Evaluation of a cellular model for assessing cytoprotection by natural chemicals - Hashim, Maha Jalal (2013)
There is considerable interest in the ability of plant-derived antioxidants to protect against oxidative damage associated with disease or exposure to toxic agents. In this study, the cytoprotection effect of the direct antioxidants quercetin (Q) and epigallocatechin-3-gallate (EGCG) and the indirect antioxidants, sulforaphane (SFN) and indole-3-carbinol (I3C) was assessed in a cellular protection assay. This assay involved two cytoprotection patterns: (a) 20-hour exposure to phytochemical followed by 5-hour exposure to t-BHP; (b) simultaneous exposure to phytochemicals and t-BHP for 5 hours. HepG2 cells were cultured to a confluent monolayer and exposed to phytochemical +/- t-BHP in serum-containing or serum-free medium, after which cell damage mediated by oxidant stress was assessed by neutral red uptake. Results showed that Q, EGCG and I3C were effective while SF was inactive and toxic to the cells by itself at high concentration during long incubation. On the other hand, short time of incubation with Q, EGCG and SF displayed identical results to prolonged exposure. However, I3C was devoid of protection activity. Moreover, results showed that serum has a major impact on antioxidant activity.